2012
DOI: 10.1186/1744-8069-8-58
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 5-HT Receptor Subtypes Enhancing Inhibitory Transmission in the Rat Spinal Dorsal Horn in vitro

Abstract: Background5-hydroxytryptamine (5-HT) is one of the major neurotransmitters widely distributed in the CNS. Several 5-HT receptor subtypes have been identified in the spinal dorsal horn which act on both pre- and postsynaptic sites of excitatory and inhibitory neurons. However, the receptor subtypes and sites of actions as well as underlying mechanism are not clarified rigorously. Several electrophysiological studies have been performed to investigate the effects of 5-HT on excitatory transmission in substantia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 73 publications
0
45
0
Order By: Relevance
“…Moreover, intrinsic GABAergic neurons also express 5-HT 3 receptors (35,36), activation of which has been shown to increase the release of GABA (37). More recently, Xie et al have shown that the 5-HT 3 receptor agonist mCPBG increases both the amplitude and frequency of GABAergic and glycinergic sIPSCs in SG neurons of rat spinal cord slices (38). Thus, increased GABA and/or glycine could act on primary afferent terminals to reduce nociceptive synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, intrinsic GABAergic neurons also express 5-HT 3 receptors (35,36), activation of which has been shown to increase the release of GABA (37). More recently, Xie et al have shown that the 5-HT 3 receptor agonist mCPBG increases both the amplitude and frequency of GABAergic and glycinergic sIPSCs in SG neurons of rat spinal cord slices (38). Thus, increased GABA and/or glycine could act on primary afferent terminals to reduce nociceptive synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The dorsal spinal cord then acts as an important pain modulation center, as it provides a place for the brainstem descending suppression system to execute its action and also regulates the transmission of nociceptive information through the intermediate neurons (Singh and Tao 2012;Takazawa and MacDermott 2010;Yang and Ma 2011). Many studies have shown that a large amount of pain-associated molecules act in the dorsal spinal cord, especially those associated with nerve pathological pain (Quan-Xin et al 2012;Wei et al 2013;Xie et al 2012;Zhu et al 2013). Besides, various neurotransmitters and neurotransmitter receptors in the dorsal spinal cord could be altered during the nerve pathological pain (Paul et al 2012;Rahman et al 2007;Wan et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that the pudendal afferent firing might be transmitted to the brain and activate the raphe nuclei that drives the descending 5-HT pathway to activate 5-HT 2 excitatory receptors on inhibitory spinal interneurons (GABAergic/glycinergic) that in turn suppress the micturition reflex. This possibility is supported by various evidence: (1) activation of presynaptic 5-HT 2A receptors on the GABAergic interneuron can enhances GABA release (Fink and Göthert, 2007), (2) 5-HT 2A receptors are present on the GABAergic or glycinergic neurons in the spinal dorsal horn (Wang et al, 2009; Xie et al, 2012) and contribute to spinal antinociception (Liu et al, 2007; Song et al, 2011), and (3) spinal 5-HT 2A receptors are involved in the antinociceptive effect induced by transcutaneous electrical nerve stimulation (Radhakrishnan et al, 2003). However, methysergide did not completely block PNS inhibition in the AA irritated bladder raising the possibility that pudendal neuromodulation is mediated in part by non-5-HT mechanisms.…”
Section: Discussionmentioning
confidence: 93%